Three Discrete Patterns of Primary Aldosteronism Lateralization in Response to Cosyntropin During Adrenal Vein Sampling - Wannachalee, Taweesak (J Clin Endocrinol Metab, 2019)
CONTEXT: Cosyntropin [ACTH (1–24)] stimulation during adrenal vein (AV) sampling (AVS) enhances the confidence in the success of AV cannulation and circumvents intraprocedure hormonal fluctuations. Cosyntropin’s effect on primary aldosteronism (PA) lateralization, however, is controversial. OBJECTIVES: To define the major patterns of time-dependent lateralization, and their determinants, after cosyntropin stimulation during AVS. METHODS: We retrospectively studied patients with PA who underwent AVS before, 10, and 20 minutes after cosyntropin stimulation between 2009 and 2018. Unilateral (U) or bilateral (B) PA was determined on the basis of a lateralization index (LI) value ≥4 or <4, respectively. Available adrenal tissue underwent aldosterone synthase–guided next-generation sequencing. RESULTS: PA lateralization was concordant between basal and cosyntropin-stimulated AVS in 169 of 222 patients (76%; U/U, n = 110; B/B, n = 59) and discordant in 53 patients (24%; U/B, n = 32; B/U, n = 21). Peripheral and dominant AV aldosterone concentrations and LI were highest in U/U patients and progressively lower across intermediate and B/B groups. LI response to cosyntropin increased in 27% of patients, decreased in 33%, and remained stable in 40%. Baseline aldosterone concentrations predicted the LI pattern across time (P < 0.001). Mutation status was defined in 61 patients. Most patients with KCNJ5 mutations had descending LI, whereas those with ATP1A1 and ATP2B3 mutations had ascending LI after cosyntropin stimulation. CONCLUSION: Patients with severe PA lateralized robustly regardless of cosyntropin use. Cosyntropin stimulation reveals intermediate PA subtypes; its impact on LI varies with baseline aldosterone concentrations and aldosterone-driver mutations.